2022
DOI: 10.1186/s12886-022-02565-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between apelin and VEGF levels in retinopathy of prematurity: a matched case–control study

Abstract: Background Although several clinical studies have analysed the relationship between the levels of vascular endothelial growth factor (VEGF) and apelin-13 in venous blood and retinopathy of prematurity (ROP), no definitive conclusions have been reached. This study aimed to investigate the relationship between apelin-13 levels and VEGF levels and ROP. Methods Differences in plasma apelin-13 and VEGF levels were analysed in two groups of infants born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A promising finding in Yang et al's study ( 22 ) indicated that some biomarkers had the potential to be detected before symptoms emerged. Despite such results, longitudinal studies with larger sample sizes are recommended to further investigate the causal relationship between these altered metabolites and ROP, and therefore, their significance in the clinical setting ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising finding in Yang et al's study ( 22 ) indicated that some biomarkers had the potential to be detected before symptoms emerged. Despite such results, longitudinal studies with larger sample sizes are recommended to further investigate the causal relationship between these altered metabolites and ROP, and therefore, their significance in the clinical setting ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…While Zhang et al and Cekemez at al. ( 48 , 52 ). both found plasma apelin levels to be significantly lower in infants with ROP as compared to those without ROP, the opposite was noted by Feng et al ( 41 ) Furthermore, this latter study found plasma apelin levels to positively correlate with ROP severity, which has also been seen in diabetic retinopathy (reference), therefore suggesting that apelin might aggregate pathological processes and be a candidate for predicting disease severity, rather than occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, published data remained inconclusive regarding the systemic levels of VEGF in association with ROP. Among preterm neonates who eventually developed ROP, some researchers found that VEGF concentrations in the early period of life in cord blood at birth and circulating blood are significantly lower than those in their non-ROP counterparts [ 72 , 85 , 86 ], while some observed the opposite results [ 87 , 88 , 89 ] and others found no difference [ 40 , 58 , 90 ].…”
Section: Cytokines: Characteristics and Actionsmentioning
confidence: 99%
“…Several studies have investigated the association between inflammatory markers and the risk of ROP, focusing on specific cytokines, such as interleukin (IL)-6, IL-8, tumor necrosis factor-alpha (TNF-α), and insulin-like growth factor (IGF) [ 18 , 19 , 20 ]. However, the results have been inconsistent, with some studies showing a significant association between elevated cytokine levels and ROP, while others have not found any correlation [ 21 , 22 ]. Furthermore, most of these studies have been retrospective, with a limited ability to establish a causal relationship between inflammation and ROP.…”
Section: Introductionmentioning
confidence: 99%